2018
DOI: 10.1108/ijem-05-2017-0122
|View full text |Cite
|
Sign up to set email alerts
|

Transnational higher education

Abstract: Purpose-The purpose of this paper is to assess the extent to which the critical relational variables of university reputation, student trust and student-university identification influence student behaviour towards transnational education partnerships. Design/methodology/approach-Students undertaking British degrees at two transnational partnership locations (Hong Kong, n ¼ 203 and Sri Lanka, n ¼ 325) completed a quantitative survey questionnaire. A conceptual model was developed and tested using structural eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 48 publications
2
22
0
2
Order By: Relevance
“…They highlight also that such independent evaluations of HEIs might reflect the use of distinct inferential bases for the evaluations. Student trust were found to be significant predictors of student identification with higher education institutions [35]. Carvalho and Mota [61] demonstrated that trust in both the HEI's personnel (faculty and staff members) and in the HEI's management (as reflected in its administrative and process policies and practices) increases students' perception of value of the HEIs, which in turn leads to student loyalty.…”
Section: Student-institutionmentioning
confidence: 99%
See 3 more Smart Citations
“…They highlight also that such independent evaluations of HEIs might reflect the use of distinct inferential bases for the evaluations. Student trust were found to be significant predictors of student identification with higher education institutions [35]. Carvalho and Mota [61] demonstrated that trust in both the HEI's personnel (faculty and staff members) and in the HEI's management (as reflected in its administrative and process policies and practices) increases students' perception of value of the HEIs, which in turn leads to student loyalty.…”
Section: Student-institutionmentioning
confidence: 99%
“…Customer loyalty is typically analysed in terms of preferences and intentions, which might be regarded as attitudinal loyalty [66]. In our study, we apply the attitudinal loyalty approach that defines loyalty as the situation in which a consumer holds a favourable view of an organisation and feels an emotional attachment to the organization [35].…”
Section: Trust As An Antecedent Of Loyalty and Reputationmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Heffernan, Wilkins and Butt [19], 'students' trust in an educational institution has been shown to have numerous positive outcomes, including confidence to select and enrol in a programme, increased student loyalty and engagement'. However, Kharouf, Sekhon and Roy [20] identify that ownership of trust ultimately belongs to the student and can be affected by the behaviours of the HEI.…”
Section: Academic Trustmentioning
confidence: 99%